Salmon feed ingridients - Atle Guttormsen (22682399) (2025)
Economic Returns of Ingredient Substitution in Salmon Feed, 1996–2024. This study quantifies the economic impact of the salmon aquaculture industry's transition from marine-based to plant-based feed ingredients over nearly three decades. We construct a Feed Cost Index for Norwegian salmon aquaculture that explicitly accounts for time-varying feed composition, using monthly commodity price data and documented formulation changes. Key findings: - Maintaining the traditional 1990 formulation (89% marine ingredients) would have increased feed costs by 59% on average during 2015–2023 - The transition generated industry savings exceeding 850 million USD annually at current Norwegian production levels - Plant-based formulations reduced feed cost volatility by 28%, improving cost predictability for producers. The dataset contains annual ingredient prices (fish meal, fish oil, soybean meal, rapeseed oil), feed composition shares, and calculated feed costs under actual and counterfactual formulation scenarios. Data sources include World Bank Commodity Markets, Statistics Norway, and published feed composition studies. This research demonstrates that economic incentives have strongly reinforced sustainability-driven changes in salmon feed formulation, with implications for evaluating novel ingredients as they enter commercial production.